Trade secrets : law and practice - Quinto, David W. (Oxford University Press, 2009)
"This work focuses on what is protectable as a trade secret, litigating trade secret actions, plaintiff's and defendant's perspectives, corporate trade secret protection plans and practices, hiring and terminating employees, criminal prosecution of trade secret misappropriation"--Provided by publisher.